Experience of the Reproductive Medicine Unit of Clinica Monteblanco with the Use of Corifollitropin Alpha in in Vitro Fertilization Cycles [Experiencia de la Unidad de Medicina Reproductiva Clínica Monteblanco Con el Uso de Corifollitropin Alfa en Ciclos de Fecundación in Vitro] - Schwarze-Meza, J (Sociedad Chilena de Obstetricia y Ginecologia, 2015)
Background: Controlled ovarian hyperstimulation (COH) is a main component of in-vitro fertilization (IVF) cycles. COH have been performed with daily exogenous gonadotropins administered, adding to treatment an additional component of stress. The appearance of a depot recombinant FSH (corifollitropin alfa) helps to reduce stress in patients undergoing IVF. No studies have shown differences in the number of retrieved oocytes or clinical pregnancy rates; however these studies have been funded by the pharmaceutical industry. Aims: To show the experience of Reproductive Medicine Unit Monteblanco with the use of corifollitropin alpha in autologous IVF cycles, in unselected patients. Methods: Our main outcome was the mean number of oocytes retrieved, and the proportion of oocytes in metaphase 2 in patients undergoing COH with corifollitropin alpha, daily recombinant FSH (rFSH), and a combination of rFSH and urinary gonadotropin. Results: We analyzed 727 IVF cycles: 270 cycles with corifollitropin alpha, 33 exclusive rFSH and 333 cycles with rFSH combination and urinary gonadotropins. We did not found any statistically significant difference in the mean number of oocytes recovered nor the proportion of metaphase two oocytes obtained. After adjusting for age, we did not find that the COH protocol influenced the mean number of oocytes recovered. Conclusion: We concluded that the use of corifollitropin alpha in autologous IVF cycles does not alter the mean number of oocytes recovered, nor the proportion of oocytes in metaphase 2.